The Influence of Organizational Behavior and Leadership Style on Employee Performance - Nurmilasari Nurmilasari; Andi Nurhidayati; Indra Saputra; Deska Canrawinata; Arisandi Arisandi; Muhammad Yusri (GENTARA: management and accounting research, 2026)
This study aims to analyze the effect of organizational behavior and leadership style on improving employee performance. In facing increasingly complex work dynamics, organizations are required to effectively manage individual and group behavior, as well as implement appropriate leadership styles to enhance employee performance. This research employs a quantitative approach, with data collected through questionnaires distributed to respondents. The data analysis techniques used include validity and reliability tests, as well as multiple linear regression analysis to examine the effect of organizational behavior and leadership style as independent variables on employee performance as the dependent variable. The results of this study indicate that organizational behavior and leadership style have a positive and significant effect on employee performance. This implies that the better the organizational behavior implemented and the more effective the leadership style applied, the higher the level of employee performance achieved. In conclusion, organizational behavior and leadership style play an important role in improving employee performance. Therefore, organizations are encouraged to create a conducive work environment, enhance communication, and adopt effective leadership styles to optimize employee productivity and performance